2016
DOI: 10.1021/acsami.6b02847
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Strontium Titanate Film as Gate Dielectric for Higher Performance and Low Voltage Operation of Transparent and Flexible Organic Field Effect Transistor

Abstract: We report that the pervoskite material, strontium titanate (STO) can be used as a gate dielectric layer of flexible and low voltage organic field effect transistor (OFET). The crystallinity, dielectric constant, and surface morphology of STO films can be controlled by the engineering of the growth condition. Under optimized growth condition, amorphous films of STO show a much better gate dielectric compared to other gate dielectrics used to date, with very small leakage current density for flexible and low vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Meanwhile, device A has a threshold voltage ( V T ) of −1 V, which is almost optimal. On the other hand, V T s of devices B and C are −11 and ~20 V, which are far from the optimal value of 0 V. It is well known that threshold voltage of OFET is strongly determined by the trap density ( N ) at the interface of dielectric and organic semiconductor of the device [ 31 ]. Low charge trap density at the dielectric/organic semiconductor interface usually benefits to low V T value.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, device A has a threshold voltage ( V T ) of −1 V, which is almost optimal. On the other hand, V T s of devices B and C are −11 and ~20 V, which are far from the optimal value of 0 V. It is well known that threshold voltage of OFET is strongly determined by the trap density ( N ) at the interface of dielectric and organic semiconductor of the device [ 31 ]. Low charge trap density at the dielectric/organic semiconductor interface usually benefits to low V T value.…”
Section: Resultsmentioning
confidence: 99%
“…Yadav and Ghosh recently reported that amorphous STO films can be used in transparent and flexible organic field effect transistor as a gate dielectric material. 40 They used STO thin films with a dielectric constant values in the range 10-30, and promising application in microelectronics.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…However, also interfaces between SrTiO 3 (STO) and organic molecules are studied increasingly using both experimental [ 4 5 ] and theoretical approaches [ 6 ]. Possible applications of STO/organic interfaces include FETs [ 7 8 ], photodiodes [ 9 ], and organic spin valves[ 10 ].…”
Section: Introductionmentioning
confidence: 99%